Characterization of effective microorganism (Phosphate solubilizing bacteria) isolated from rice-field soils / Nurul ‘Atiqah Rosnan - Rosnan, Nurul ‘Atiqah (Faculty of Plantation and Agrotechnology, 2018)
Methods that are not just efficient, but also have low cost of agricultural input, safe, supplementary, renewable and environmental friendly are nowadays being concern. This study is focused on identifying either with the inoculations of Phosphate Solubilizing Bacteria (PSB) will really give effects to the solubilisation of phosphorus in soil and become available for plant uptake or there is no significance at all. To address this, four treatments are set up which are Merlimau soil (T0), Merlimau soil with Phosphate Solubilizing Bacteria (PSB) (T1), Tanjong Karang soil (T2), and Tanjong Karang soil with PSB (T3). Available P for the treatments and the value of soil pH are being taken as the parameter. Besides, the growth performance of rice plants was also recorded with the measurement of plant height, number of tillers and number of leaves on weekly for five weeks. The soil analysis for available P and the soil pH was found to have significant increase when treated with PSB as shown for the results of T1 and T3. The plant analysis for the growth performance of rice plants also shows that better growth of plant for the soils that been treated with PSB. Thus, the application of PSB to the rice-field soil can increase P availability and reduce the acidity of the soil. In addition, it gives effect to the performance of the rice growth where this study shows results in increasing of plant height, higher development of tillers and plant leaves compared to the soils that does not treated with PSB. However, to ensure the application of this technique can produce significant effects, several effective considerations must be taken.